2015
DOI: 10.1111/meta.12155
|View full text |Cite
|
Sign up to set email alerts
|

Video Feedback in Philosophy

Abstract: Marginal comments on student essays are a near-universal method of providing feedback in philosophy. Widespread as the practice is, however, it has well-known drawbacks. Commenting on students' work in the form of a video has the potential to improve the feedback experience for both instructors and students. The advantages of video feedback can be seen by examining it from both the professor's and the student's perspective. In discussing the professor's perspective, this article shares observations based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 4 publications
5
43
0
1
Order By: Relevance
“…Moore and Filling (2012) found that, when providing video feedback, markers made fewer brief suggestions and corrective comments, instead elaborating on points and providing specific details. Markers using video feedback were also more likely to provide more detailed comments on the positive aspects of students' work (Lamey 2015;Parton, Crain-Dorough, and Hancock 2010;Thomas, West, and Borup 2017).…”
Section: Characteristics Of Video Feedbackmentioning
confidence: 99%
See 3 more Smart Citations
“…Moore and Filling (2012) found that, when providing video feedback, markers made fewer brief suggestions and corrective comments, instead elaborating on points and providing specific details. Markers using video feedback were also more likely to provide more detailed comments on the positive aspects of students' work (Lamey 2015;Parton, Crain-Dorough, and Hancock 2010;Thomas, West, and Borup 2017).…”
Section: Characteristics Of Video Feedbackmentioning
confidence: 99%
“…Some researchers suggest that video feedback fundamentally shifts the focus of feedback from the surface-level mechanics of writing to more substantive, global aspects of students' performance (Henderson and Phillips 2015;Lamey 2015;Orlando 2016;Thompson and Lee 2012;Vincelette and Bostic 2013). Under this characterisation, surface-level feedback focuses on superficial or mechanical concerns such as spelling and grammar, syntax and referencing, while substantive feedback addresses deeper and more conceptual academic skills such as argument, analysis and synthesis.…”
Section: Characteristics Of Video Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…This is partly because the use of the voice allows for more complex and in-depth feedback which is not limited by the written medium. Teachers can contextualise feedback and provide more guidance on how to correct the work (Lamey 2015).…”
Section: Enjoymentioning
confidence: 99%